2018
DOI: 10.1111/imj.13617
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the role of magnetic resonance imaging post‐neoadjuvant therapy for breast cancer in the NEONAB trial

Abstract: MRI appears more accurate for predicting pCR in HER2+ disease than other subtypes and in cancers with Ki-67 ≥ 15% compared to those with Ki-67 < 15%. Accuracy of MRI in our HR+, RS ≥ 25 cohort is comparable to previous reports of unselected HR+ disease. MRI post-NST should be interpreted in conjunction with HER2 status and Ki-67 index of the primary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The Luminal B disease cohort were all hormone receptor (HR) and HER2 positive in our cohort, which may have influenced this outcome. Murphy et al 24 found MRI accuracy to be much higher in HER2-positive breast cancer. Our small HER2/neu sample size (n = 8) limits our ability to comment definitively on this subtype.…”
Section: Discussionmentioning
confidence: 98%
“…The Luminal B disease cohort were all hormone receptor (HR) and HER2 positive in our cohort, which may have influenced this outcome. Murphy et al 24 found MRI accuracy to be much higher in HER2-positive breast cancer. Our small HER2/neu sample size (n = 8) limits our ability to comment definitively on this subtype.…”
Section: Discussionmentioning
confidence: 98%
“…It is interesting to note, however, our results suggested that the odds of imaging-pathological discordance in luminal B and HER2-enriched tumors was about 6 and 12 times higher than in luminal A subtype, respectively. Some authors proposed that MRI accuracy was higher in HER2-positive and triple-negative breast cancer and less in luminal breast cancer (9,19,26), whereas others proposed that MRI accuracy significantly decreased in patients treated with HER2-targeted agents, resulting in an overestimation of the extent of the residual lesions due to the increase in neovascular permeability (27), which may lead to overtreatment in this subtype. A consensus has not yet been reached at present on this issue.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of HER2-positive tumor, the shrinkage pattern has been found to be a stronger predictor of pCR than size changes and absence of residual enhancement with a concentric shrinkage pattern predicting pCR with 96.6% specificity and 59.1% sensitivity [36]. In addition, higher Ki-67 levels and nuclear grade tumors have higher MRI accuracy [31,33,[37][38][39]. Lobular carcinoma or ductal carcinoma mixed with lobular carcinoma components is more likely to cause preoperative MRI false negatives and greater size discrepancy when compared with pathological specimens [40,41].…”
Section: Factors Affecting Mri Accuracy For Pcrmentioning
confidence: 99%